Improving an online higher education pharmacology course based on students’ perception - Traetta, Marianela E.; Viola, María S.; Minoia, Juan Mauricio (International Journal of Basic & Clinical Pharmacology, 2023)
Background: The COVID-19 pandemic outbreak transformed education thoroughly. Our in-classroom Pharmacology course had to be adapted precipitously into a completely online modality. Hence, we aimed to evaluate its efficacy for learning and improve it based on our students’ perception. Methods: Semi-open questionnaires were designed and applied at the end of the 2020 and 2021 courses to assess students’ satisfaction on the following fields: eLearning platform, lectures, synchronous discussion section, asynchronous collaborative work, and assessments. Data from the first online course was analyzed and evidence-based improvements were performed for the 2021 course. Quantitative comparison of cohorts was carried out. Furthermore, students’ perception from the last in-person course (2019) was analyzed. Results: The 2019-course questionnaire demonstrated a good acceptance towards an incipient use of the virtual campus. Comparison of the complete online cohorts revealed a significant increase in positive answers in six items: complementarity of lectures with discussion sections (85% vs. 100%), teaching strategy (30% vs. 84%), adequacy of faculty’s role (47% vs. 79%), pre- and post-class activities (30% vs. 55%), wording of exercises (30% vs. 55%) and assessments (50% vs. 97%). Moreover, a modification of the students’ requests expressed in the comment section was observed. Conclusions: Custom-designed semi-open questionnaires used to evaluate students’ perception and receiving feedback on the Pharmacology course provided high quality information to promote student-oriented changes that allowed for an improvement in the teaching-learning process.